Survey data on heterogeneity in consumers’ food choice in eastern India - Ynion, Jhoanne; Custodio, Marie Claire; Samaddar, Arindam; Mohanty, Suva Kanta; Cuevas, Rosa Paula; Ray (Chakravarti), Anindita; Demont, Matty (Elsevier, 2021)
A consumer survey was conducted in eastern India in 2017 to understand the heterogeneity of consumers’ food choice. Face-to-face interviews were conducted among urban and rural consumers from low- and middle-income households in Odisha and West Bengal, eastern India, using a structured questionnaire. A multi-stage sampling procedure was implemented with stratified random sampling as the first stage and systematic sampling as the second stage. The survey data comprise responses from 501 respondents who have active involvement in grocery purchase decision-making and/or in meal planning or cooking for the household. The survey generated a dataset that was used to unravel five sources of heterogeneity (5Ws) in gastronomic systems that affect consumers' diets: (i) socioeconomic characteristics of the target population (who); (ii) food environments (where); (iii) eating occasions (when); (iv) consumed dishes (what); and (v) ingredient attributes and consumer attitudes towards food (why). The approach and analyses are elaborated in the article “Unraveling heterogeneity of consumers’ food choice: Implications for nutrition interventions in eastern India”. Data from the survey can be further used to design behavioral experiments and interactive food choice tablet applications to elicit behavioral intentions in food choice.